PENGEMBANGAN KURIKULUM DI INDONESIA DALAM MENGHADAPI TUNTUTAN ABAD KE-21 - Diah Rusmala Dewi (AS-SALAM, 2019)
This article aims to examine curriculum development in Indonesia in facing the demands of 21st century competencies. The method used in this research is literature study where the author tries to find, compile and analyze various information through various related sources. The rapid development of information and communication technology as well as free competition between countries in all fields has marked the start of the 21st century. This has implications for the world life that students face today is different and much more complex than the previous era. The results of this study are: 21st century curriculum development requires students to learn more and be proactive so that they have 21st century competencies which include: communication, collaboration, critical thinking and problem solving, creativity and innovation skills and mastery of ICT which require higher order thinking skills or Higher Order Thinking Skills (HOTS). The expected positive impact of this article is an increase in the quality of education in Indonesia so as to create an educated society in the future who is able to face the challenges of an increasingly competitive era.